Effect of Safety Education to Workers Productivity at The Electric Welding Workshop - Akmal Fauzi; Vania Bintang Assyifa; Khayla Diandra Fatima Muhammad; Emilia Indri Artanti; Tharada Phuttharak; Irna Mufidatul Himmah (Universitas Negeri Semarang, 2023)
Productivity is generally defined as a measure of the amount of output generated per unit of input. The aim of this research is to analyse the effect of the fulfilment of Occupational Safety and Health as well as the ability, experience, motivation, and discipline of workers on the probability of low productivity in the Electric Welding Workshop. The method used in this study was a qualitative descriptive method with questionnaires and observation sheets. The result showed that the Electric Welding Workshop workers felt that the fulfilment of OSH aspects, their ability, experience, motivation, and discipline impacted their productivity. The study concludes that Electric Welding Workshop is not included in low productivity because it produces stuffs with quality and quantity according to standards, although it has not yet fulfilled the aspects that increase productivity.